Gerakan Solidaritas Pada Masa Pandemi Covid-19 Sebagai Wujud Wajah Sosial Gereja - Fransiskus Xaverius Sugiyana; Nerita Setiyaningtiyas (Jurnal Ledalero, 2022)
Abstract: This research was a descriptive qualitative study based on the pastoral work of the data-driven concerning Church experiences during the Covid-19 pandemic.  Departing from various solidarity initiatives, this study showed that the efficiency and effectiveness of pastoral work began with a social analysis of the problems. The mapped problems brought an insight on how pastoral plan should be done. The hope is that the arranged programs can have measurable results and real impact. The first focus of this research was the pattern of solidarity movements. The second focus is the face of the Church that appears in the community and society.  Data collection employed descriptive qualitative methods. Data analysis used content analysis approach.  The first findings showed that parishioners of the kevikepan Semarang concerned with economic recovery and psychological assistance. The second finding showed that the solidarity movement revealed the social faced of the Church. In the missionary spirit, the Church showed sensitivity to social issues due to the Covid-19 pandemic. The Church also appeared to have a spirit of compassion, care and a high willingness to share. The involving people with all backgrounds who were in solidarity movement was a sign of the presence of the Kingdom of God. The act of solidarity can really bring transformation for each person involved in it.Key words: Pastoral Theology; Capital Social; Altruism; Catholic Social Teaching; Semarang